Potential Bankruptcy of Digital Companies in Indonesia: Analysis of Market Aspects and Financial Aspects Using Springate and Grover Methods - Novi Diah Wulandari; Winike Kushindrajati Aprilia (Economics, Business, Accounting & Society Review, 2023)
Digital companies are companies that are growing very rapidly, but face many problems that can lead to bankruptcy. Therefore, bankruptcy prediction is an important topic that must be considered. If a company wants to survive and develop, it must pay attention to financial and market aspects. Therefore, in this survey, we selected six digital companies listed on the IDX between 2018 and 2021 as samples using the observation method. The analytical method used is Springate and Grover because it is considered good for knowing the financial distress of a company. This study aims to determine the condition of the company for the progress and sustainability of the company and help investors to determine investment. In addition, this study also aims to find out what method is right for predicting the financial distress of digital companies listed on the Indonesia Stock Exchange. Financial findings using the Springate approach show 3 companies in the bankrupt category, 1 potentially bankrupt and 2 healthy. Instead, according to Grover's method, 1 company is bankrupt and 5 are healthy. The accuracy rate for the Grover method is 83% with a low error rate of 17% so that it can be said that the Grover method is considered better for predicting bankruptcy. From a market perspective, all the companies in this study have excellent market potential. Companies must pay attention to financial and market aspects to avoid bankruptcy and develop better.